Differential characteristics and management of pseudoseptic arthritis following hyaluronic acid injection is a rare complication: a systematic review. Issue 2 (3rd November 2020) - Sedrak, Phelopater; Hache, Philip; Horner, Nolan S; Ayeni, Olufemi R; Adili, Anthony; Khan, Moin
Abstract : Importance: Acute pseudoseptic arthritis is a rare complication of hyaluronic acid (HA) injections that is not well documented in the literature. Practitioners initially suspect the symptoms of this complication to represent septic arthritis, cautiously prescribing antibiotics. This review identifies that time to presentation of symptoms postinjection, negative cell cultures and lack of crystallisation could be used as differentials to suspect pseudoseptic arthritis and to prescribe anti-inflammatory drugs while closely monitoring change of symptoms. Objective: The purpose of this study was to describe the presentation, diagnosis and treatment of pseudoseptic arthritis. Evidence review: A systematic review of the literature was conducted for studies reporting the use of HA injections for osteoarthritis resulting in pseudoseptic arthritis using the electronic databases MEDLINE, Embase and PubMed. Pertinent data were abstracted from the search yield. A unique case of a pseudoseptic reaction is also presented. Findings: A total of 11 studies (28 cases), all of level IV and V evidence were included in this review. Reported cases of pseudoseptic arthritis in the literature present with severe joint pain (100%), effusion (100%), inability to weight-bear, functional impairment, and occasionally fever (22.2%). C reactive protein and erythrocyte sedimentation rate are generally elevated (71.4% and 85.7%, respectively), and leucocytosis above 10 000 was less common (50%). All reported cases in the literature identified aseptic growth on arthrocentesis, despite four cases (15.4%) reporting synovial leucocyte counts above 50 000. The presented case is the highest reported leucocyte count at 1 74 960 cells/mm 3 . Conclusions and relevance: Acute pseudoseptic arthritis is rare, but a number of cases have been reported in the literature. A high degree of suspicion for pseudoseptic arthritis may be maintained in patients who present under 72 hours following HA injection. Initial antibiotic treatment, along with anti-inflammatory medications until cultures are confirmed to be negative at 5 days, is a cautious approach. However, the strength of this conclusion is limited by the few reported cases. Ultimately, this review is intended to inform practitioners of the symptoms, diagnosis and treatment of this complication, such that it could be safely differentiated from septic arthritis. Level of evidence: IV.